2020
DOI: 10.32890/mmj.21.2017.9049
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Luckiness: How Crazy Are Malaysian Chinese Towards Car Plate Number “8”?

Abstract: The Chinese society is well-known for its obsession towards number “8”. Eight is the luckiest number to the Chinese as its pronunciation resembles the meaning of prosperity, wealth or fortune. Prior research estimating the marginal effect of “8” on winning bid prices of car plate numbers attributes the positive impact of “8” on bid prices to superstitious value. However, the estimated positive effect could also be attributed to Veblen goods and future resale consideration. Thus, an upward bias might exist in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Many studies have asserted that Malays have lower individualism, power distance, higher feminism and uncertainty avoidance, leading to lower risk-taking (Chen et al, 2015;Ashraf et al, 2016). Malays are often perceived as more oriented towards harmony and relationship building, while Chinese are believed to be more materialistic (Lim, 1998). Tehseen and Anderson (2020) concluded that Malay entrepreneurs are closely attached to their customs and create a less individualistic culture, which adversely affects firm performance.…”
Section: Audit Committee Ownershipmentioning
confidence: 99%
“…Many studies have asserted that Malays have lower individualism, power distance, higher feminism and uncertainty avoidance, leading to lower risk-taking (Chen et al, 2015;Ashraf et al, 2016). Malays are often perceived as more oriented towards harmony and relationship building, while Chinese are believed to be more materialistic (Lim, 1998). Tehseen and Anderson (2020) concluded that Malay entrepreneurs are closely attached to their customs and create a less individualistic culture, which adversely affects firm performance.…”
Section: Audit Committee Ownershipmentioning
confidence: 99%